Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

hrcheerlove

  • 3 years ago

Solve the following system of equations. 2x + y = 3 x = 2y - 1

  • This Question is Closed
  1. Hero
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Hint: 2(2y - 1) + y = 3

  2. hrcheerlove
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    I don't know lol

  3. jennychan12
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    plug in x for x in the first equation. 2(2y-1) +y = 3 now that you have everything in terms of y solve for y then plug in y for x = 2y-1

  4. jennychan12
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    4y - 2 +y = 3 5y = 5 y =1 x = 2-1 x=1

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy